1975
DOI: 10.1042/bj1450225
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic acid poymerase of BHK-21/C13 cells. Heterogeneity, molecular asymmetry and subcellular distribution of the enzymes

Abstract: Nuclear and cytoplasmic fractions were prepared from exponentially-growing BHK-21/C13 cells; DNA polymerase was extracted from them and analysed by gel filtration and sucrose-density-gradient centrifugation. DNA polymerase I is heterogeneous comprising species covering a considerable range of molecular weights. These have been tentatively identified as four subspecies of apparent molecular weights 900000-1000000 (IA), 460000-560000 (IB), 270000-320000 (IC) and 140000-200000 (ID), as assessed by gel filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…We had previously observed two major sedimentation forms of DNA polymerase in crude extracts of Drosophilu embryos (7.3 S and 9.0 S) and had demonstrated that a third form (5.5 S) was a proteolysis product of the 7.3-S enzymes 1121. DNA polymerase-a from calf thymus gland, rat liver, rat spleen [23], and BHK-21/C13 cells [24] and DNA polymerase-y from mouse myeloma cells 1221 have similar sedimentation coefficients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We had previously observed two major sedimentation forms of DNA polymerase in crude extracts of Drosophilu embryos (7.3 S and 9.0 S) and had demonstrated that a third form (5.5 S) was a proteolysis product of the 7.3-S enzymes 1121. DNA polymerase-a from calf thymus gland, rat liver, rat spleen [23], and BHK-21/C13 cells [24] and DNA polymerase-y from mouse myeloma cells 1221 have similar sedimentation coefficients.…”
Section: Discussionmentioning
confidence: 88%
“…Multiple forms of DNA polymerase from other organisms are also resolved by DEAE-cellulose chromatography, e.g. DNA polymerase-a from calf thymus gland [24], rat liver 1231, and Xrnopus embryos [25] and DNA polymerase from Euglena [I41 and from yeast [lo]. Sedimentation of the DEAE-cellulose-purified DNA polymerases on glycerol velocity gradients showed forms of 5.5-7.3 S (enzyme I), 7.3-8.3 S (enzyme II), and 7.3 -9.0 S (enzyme 111).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity of the enzyme activity has been observed in a variety of tissues and cells such as calf thymus [34,54,55], rat liver [34], mouse myeloma [56,57] BHK cells [58] and rabbit bone marrow [59]. This heterogeneity may be due to aggregation [26], proteolysis or possibly to association with other proteins of the replication complex and these probably account for some of the difficulties in purification.…”
Section: Eukaryote Dna Polymerasesmentioning
confidence: 99%
“…Heterogeneity of DNA polymerase a [DNA nucleotidyltransferase (DNA-directed), EC 2.7.7.7] has commonly been observed during its purification from a variety of cell systems (1)(2)(3)(4)(5). This has hampered the establishment of the physical structure of DNA polymerase a and there is, as yet, no general agreement on the physical properties ofthe core enzyme (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Subcellular Fractionation Procedure. The separation of the cell homogenates into the nuclear and postmicrosomal supernatant fractions was according to our published procedures (3,21,22). In this case, however, the homogenization was performed in STKMD buffer (250 mM sucrose/50 mM Tris-HCl, After' loading, the native DNA-cellulose column was washed with 10 column volumes of TDE buffer/0.…”
mentioning
confidence: 99%